The Mapping of a Russian War: The Atlas of the Principality of Polatsk by Stanisław Pachołowiecki (1580) - Niedźwiedź, Jakub, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This volume is a comprehensive analysis of the Atlas of the Principality of Polatsk (1580), one of the oldest cartographic representations of the military conflict between Russia (Muscovy) and the Western world. Its author, the Polish royal cartographer Stanisław Pachołowiecki, drew the maps at the beginning of the Livonian War (1579-1582) when the Polish-Lithuanian army liberated the Lithuanian and Livonian lands from Muscovian occupation. The Mapping of a Russian War focuses on the military aspects of the maps, their political and propaganda use, and the Early Modern construction of the past through maps. The authors present an innovative approach to these maps, rarely examined by the international research community.